Assessing the incidence of AVN due to treatment for all at one tertiary children's hospital. (24th May 2012) - Murphy, S; Grainger, J; Mughal, Z; Zenios, M; Reeves, M
Abstract : Aims: To assess the incidence of Avascular Necrosis (AVN) in Children receiving treatment for all. Methods: The notes of patients who developed AVN due to treatment for ALL were reviewed. Patients were male and females, aged 3-14 years and received regimens A, B or C as per UKALL. 2, 8 and 3 patients received these regimens respectively. Types of ALL included Common ALL, Pre-B cell and T cell ALL. Two of the patients reviewed relapsed with ALL. Patients were of different ethnic backgrounds, The majority were white British. The time between initial diagnosis of ALL and an initial symptom suggesting AVN was recorded as was the timing of the first radiological diagnosis of AVN. AVN was confirmed by XR and or MRI scan. The location of the AVN was also noted in each patient and any intervention carried out or medication given to alleviate the AVN was also recorded. Results: Incidence of AVN: 18.57%(13/70 patients) (figure 1). The mean age of diagnosis with ALL of those who developed AVN: 12 years. – Females 11.75 Years. – Males 12.4 years. Mean time from initial diagnosis of ALL to first symptom of AVN*: 19.23 Months. – Females 21.5 Months. – Males 15.6 Months. Mean time from Initial diagnosis of ALL to radiological diagnosis*: 30 months. – Females 32.13 Months. – Males 26.6 Months. *This included 2 patients who relapsed with leukaemia. Incidence of AVN in Females Vs Males (figure 2): The most common area for occurrence of AVN was the hips, followed by the knees and shoulders equally, and then the wrist and pelvis. 9/13 patients with a radiological diagnosis of AVN received an intervention. Interventions Carried out for AVN (figure 3): Oral Medications Given to Relieve AVN (figure 4): Conclusions: – Dexamethasone increases incidence of AVN-The majority of AVN patients had dexamethasone reduced or replaced with prednisolone to reduce AVN. – Females developed AVN earlier than males. – Receiving chemotherapy and the intensity of treatment increased incidence of AVN. – Older the age of the child at diagnosis greater the risk for development of AVN. – The majority of patients who developed AVN required an intervention.